2005
DOI: 10.1111/j.1365-2141.2005.05728.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome: an under‐recognised immune‐mediated complication of non‐myeloablative allogeneic haematopoietic cell transplantation

Abstract: SummaryNephrotic syndrome (NS) is an extremely rare complication of myeloablative allogeneic haematopoietic cell transplantation (HCT) that usually occurs in association with chronic graft-versus-host disease (C-GVHD). We observed an unexpectedly high incidence of NS in a cohort of 163 consecutive patients undergoing non-myeloablative HCT from a related human leucocyte antigen-compatible donor. Seven patients developed NS at a median 318 d post-transplant (range 119-1203 d; cumulative incidence 6AE1%). The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
3
62
4
Order By: Relevance
“…Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed. 4,6,22,29 Nevertheless, resolution of graft-versus-host disease and post hematopoietic cell transplant membranous glomerulonephritis with this anti-B-cell agent supports the hypothesis that B-cell alloreactivity may play a role in both of these entities. 16,35,37 Interestingly, our study also identified two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed. 4,6,22,29 Nevertheless, resolution of graft-versus-host disease and post hematopoietic cell transplant membranous glomerulonephritis with this anti-B-cell agent supports the hypothesis that B-cell alloreactivity may play a role in both of these entities. 16,35,37 Interestingly, our study also identified two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 65%
“…[4][5][6][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29] In our series, among seven patients with membranous glomerulonephritis, all five patients with allogeneic transplants had evidence of chronic graft-versushost disease, (in the non-membranous glomerulonephritis cohort, only three out of eight patients had chronic graft-versus-host disease). Importantly, we also present two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Numerous descriptive studies, derived from groups of kidney core biopsy specimens from hematopoietic cell transplant recipients with renal dysfunction, have characterized the most common types of glomerulonephritis in hematopoietic cell transplant patients. 8,[10][11][12][13][14][15][16][17][18] These include membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis. In addition, acute and chronic thrombotic microangiopathy, or 'transplant-associated thrombotic microangiopathy,' has been shown to occur commonly in hematopoietic cell transplant recipients, 8,14,[17][18][19][20][21][22][23][24][25] with smaller reported numbers of membranoproliferative glomerulonephritis, proliferative glomerulonephritis, ANCA-associated glomerulonephritis, and IgA nephropathy.…”
mentioning
confidence: 99%
“…Renal biopsy was performed in four cases and revealed MN. 8 Because the vast majority (80%) of all cases reviewed in this study, aside from the mentioned cohort study, were myeloablative (data not shown) and the preparative regimen was not reported in several of the remaining cases, other authors claimed that a greater risk for NS posed by RIC than myeloablative preparation cannot be supported by this analysis, and hence follow-up of larger cohorts is warranted. 1 Figure 1 Segmental sclerosis at the origin of the tubular pole (tip lesion) (periodic acid Schiff, Â 400).…”
mentioning
confidence: 62%